Bahasa Inggrist - rayhan tantu; Titin Dunggio; Niluh Arwati (LPPM Universitas Bina Mandiri Gorontalo, 2020)
Excess weight can cause changes to the body's cells, making the body's cells resistant to the hormone insulin. This can cause blood glucose levels to increase. This study aims to determine blood glucose levels in obese patients and the factors that influence them. This study aims to assess blood glucose levels in obese patients at the North City Health Center and the factors that affect them.The method in this study uses a descriptive quantitative approach. The type of data used is primary data from research results of blood glucose levels in obese patients and secondary data in data from the literature, books, questionnaires, and medical record books. The sampling technique in this study used accidental sampling, with a total sample of 29 people.The results showed that from 29 obese patients, there were 24 people or 82.8% whose blood glucose levels were abnormal, while five people, or 17.2%, had normal blood glucose levels. Factors that affect blood glucose levels in obese patients are gender, age, physical pattern (Body Mass Index/BMI), physical activity, and eating patterns (number of calories). Suggestions to the next researcher are suggested to examine blood sugar levels between the obese and non-obese groups as a comparison.